In the shadow of the monster: gothic narratives of violence prevention - Skott, Sara (Critical criminology, 2021)
This article examines narratives by professionals working on preventing gender-based violence in Sweden through a Gothic lens. It draws on interviews with authorities responsible for preventing gender-based violence in one region of Sweden and explores the way national policies are translated into regional action. Our analysis shows how the "reel" is adopted by the professionals and becomes a part of the "real," resulting in implications for policy. By looking at the participants’ narratives through a Gothic lens, this article argues that local-level professionals working to prevent violence frame gender-based violence as a problem of two "othered" groups: the "Immigrant Other" and the "Rural Other." Through a narratological strategy of illumination and obscurity, these groups of offenders are rendered both uncanny and monstrous by the respondents—a monstrosity that obscures any violence occurring outside this framing. The problem of gender-based violence is relegated from the site of the mundane to the sphere of the monstrous.